PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Andino Pratama; Rina Yuniarti; Ahmad Junaidi (ICMA Nasional, 2023)
This study aims to examine the Effect of Good Corporate Governance on firm value in mining companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The population in this study consisted of 71 companies. The sample technique selected based on certain criteria using purposive sampling was 15 companies.This research is a quantitative research with secondary data. The data analysis technique uses multiple linear regression analysis which is processed using the SPSS (Statistical Product And Service Solution) application. Methods of data collection using data documentation.The partial results show that managerial ownership has a negative and significant effect on firm value, institutional ownership has a negative and significant effect on firm value, independent board of commissioners has a positive and insignificant effect on firm value.